2015
DOI: 10.4103/0253-7613.161269
|View full text |Cite
|
Sign up to set email alerts
|

Calotropis procera : A potential cognition enhancer in scopolamine and electroconvulsive shock-induced amnesia in rats

Abstract: Objectives:Present study evaluates the effect of Calotropis procera (Apocynaceae) dry latex on cognitive function in rats using scopolamine and electroconvulsive shock (ECS) induced amnesia model.Materials and Methods:Male Wistar rats were pretreated with 200, 400 and 800 mg/kg of C. procera dry latex in scopolamine-induced amnesia model. Dose showing maximum effect in cognitive performance was selected and further evaluated using scopolamine and ECS-induced amnesia model for its effect on neurochemical enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Scopolamine is capable of inducing various behavioural changes in several animal species due to its anticholinergic effect leading to the depletion of acetylcholine neurotransmitter. 17,19 In our study the Rosuvastatin group showed a considerable neuroprotection in response to Cook's Pole Climbing Response apparatus and Passive Avoidance Response apparatus compared to the Control group but the improvement in dementia was not as pronounced as the Standard treatment group. The rats pretreated with Rosuvastatin showed amelioration of memory functions at day 5 when amnesia was induced by Scopolamine.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Scopolamine is capable of inducing various behavioural changes in several animal species due to its anticholinergic effect leading to the depletion of acetylcholine neurotransmitter. 17,19 In our study the Rosuvastatin group showed a considerable neuroprotection in response to Cook's Pole Climbing Response apparatus and Passive Avoidance Response apparatus compared to the Control group but the improvement in dementia was not as pronounced as the Standard treatment group. The rats pretreated with Rosuvastatin showed amelioration of memory functions at day 5 when amnesia was induced by Scopolamine.…”
Section: Discussionmentioning
confidence: 50%
“…As soon as the rat climbed the pole, both the buzzer and foot-shock were switched off. 18,19 Escape latency in seconds was recorded as end point measure.…”
Section: Cook's Pole Climbing Apparatusmentioning
confidence: 99%
“…These results imply that these animals display depressive-like behaviours after being exposed to CUMS. In the current study, EAM at a dosage level of 300 mg/kg diminished all CUMS-induced depression-like behaviours in every test scenario [66][67][68]. It is interesting to note that EAM (300 mg/kg) boosted the CUMS-induced decline in the swimming behaviour in rats during FST.…”
Section: Discussionmentioning
confidence: 59%
“…These results imply that these animals display depressive-like behaviours after being exposed to CUMS. In the current study, EAM at a dosage level of 300 mg/kg diminished all CUMS-induced depression-like behaviours in every test scenario [ 66 – 68 ].…”
Section: Discussionmentioning
confidence: 93%
“…This type of work is not reported thus earlier reports on antipsychotic action of FDCG and ADCG samples are not cited. However, reports on its effect on decreasing the marker neurochemical enzyme activity in scopolamine and ECS-induced amnesia model suggested the role of C. procera dry latex in cognition enhancement (Malabade & Taranalli 2015).…”
Section: Mk 801 Induced Hyperactivitymentioning
confidence: 99%